2021
DOI: 10.1039/d0ew00776e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short- and long-term exposure on the biodegradation capacity of activated sludge microbial communities in ready biodegradability tests

Abstract: The output of ready biodegradability tests (RBTs), that are extensively used to screen the potential of chemicals to be biodegraded, can be influenced by exposure of microbial communities to organic chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…At least 71 bacterial strains from many different habitats worldwide are involved in caffeine biodegradation, possibly sustained by ancient metabolic pathways for methylxanthines (Summers et al, 2015;Vega et al, 2021). where a 2-month pre-exposure period enhanced metformin degradation, correlating with an increase in bacterial community diversity, composition and activity (Dalmijn et al, 2021).…”
Section: Kinetics Of Micropollutants Biotransformation In Stream Wate...mentioning
confidence: 99%
“…At least 71 bacterial strains from many different habitats worldwide are involved in caffeine biodegradation, possibly sustained by ancient metabolic pathways for methylxanthines (Summers et al, 2015;Vega et al, 2021). where a 2-month pre-exposure period enhanced metformin degradation, correlating with an increase in bacterial community diversity, composition and activity (Dalmijn et al, 2021).…”
Section: Kinetics Of Micropollutants Biotransformation In Stream Wate...mentioning
confidence: 99%
“…However, it is reasonable to expect that microbes in many compartments have been exposed to industrial and naturally occurring chemicals. It has been suggested that including acclimation and adaptation in biodegradability tests may also reduce the variability often observed in tests using different inocula (Dalmijn et al, 2020 ). Taking account of adaptation processes in simulation tests would more accurately test the inherent degradability of a substance (Table 3 ).…”
Section: Major Challenges By Themementioning
confidence: 99%